Impelementation of Marketing Strategies as an Effort to Increase Costumer Loyalty at Dapur Cita Rasa Berkah Sukorejo - Oktaviani, Lusi; Hafid, Moh (Dinasti Publisher, 2025)
The culinary business is a crisis-resistant business because food is a basic human need. With the growth of the culinary business, Kopontren Musa’adah owned by Pondok Pesantren Salafiyah Syafi’iyah Sukorejo seized this opportunity by opening a culinary venture named Dapur Cita Rasa Berkah. To increase consumer loyalty, Dapur CRB uses the 7P marketing mix strategy, including product, price, place, promotion, people, process, and physical evidence. Using a qualitative descriptive research method, this study found that Dapur CRB utilizes members of Kopontren Musa’adah for promotions, offers a varied menu selection, is located in a densely populated residential area with an attractive layout for dining, relaxing, and meetings, provides Cash On Delivery (COD) service, and despite having many close competitors, conducts price comparisons directly in the field. They also offer packaging options tailored to the price for take-away purchases, and all tasks are carried out by 10 employees. The challenge faced is that the number of employees at Dapur Cita Rasa Berkah is only 10 people, divided into 2 work shifts, which is not proportional to the orders received, and the lack of understanding among employees regarding marketing strategies.